δ(1)-Pyrroline-5-carboxylate reductase as a new target for therapeutics: inhibition of the enzyme from Streptococcus pyogenes and effects in vivo - Forlani, Giuseppe (2011)
Compounds able to interfere with amino acid biosynthesis have the potential to inhibit cell growth. In both prokaryotic and eukaryotic microorganisms, unless an ornithine cyclodeaminase is present, the activity of δ(1)-pyrroline-5-carboxylate (P5C) reductase is mandatory to proline production, and the enzyme inhibition should result in amino acid starvation, blocking in turn protein synthesis. The ability of some substituted derivatives of aminomethylenebisphosphonic acid and its analogues to interfere with the activity of the enzyme from the human pathogen Streptococcus pyogenes was investigated. Several compounds were able to suppress activity in the micromolar range of concentrations, with a mechanism of uncompetitive type with respect to the substrate P5C and non-competitive with respect to the electron donor NAD(P)H. The actual occurrence of enzyme inhibition in vivo was supported by the effects of the most active derivatives upon bacterial growth and free amino acid content.